Preparation of pH test paper for routine pH determination. - Villanueva, Razelle May Layson (2007.)
The use pf pH test papers in laboratories is indispensable despite the emergence of modern and sophisticated way of pH measurement such as pH meters. The preparation of pH test papers showed promising application in pH measurement and can serve as a good substitute for pH meters in routine pH determination. The prepared pH test papers are capable of determining pH of a solution for every 0.2 - 0.5 change in pH., Paper impregnated with bromoscresol purple indicator showed a color transition of yellow to grayish - brown to purple from pH 5.2 -6.8. Bromophenol blue impregnated paper illustrated a color transition of yellow to green cyan from pH 6.2 - 8.1. While paper impregnated with phenolphthalein indicator showed a color transition of colorless to pink from pH 8.0 - 10.0. Paper impregnated with universal indicator showed a wide range of color changes from 1.0-14.0. The said paper showed a color transition of red to orange to green to blue purple. Results showed that the impregnation of varying dye concentration into the paper produces varying intensity of color while immersion time of the paper in the dye solution showed no significant effect on the color produced. Spectrophotometric analysis of the prepared pH test paper showed that the amount of dye impregnated on the paper surface increases with increasing dye concentration. The color chart prepared for the pH test showed high precision for pH determination. A survey conducted to evaluate the accuracy of the color chart showed that the mean pH value determined using the prepared pH test papers was within the pH range presented by the color chart.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: pH Test Papers